Upper gastrointestinal stenting during the SARS-CoV-2 outbreak: impact of mitigation measures and risk of contamination for patients and staff - Rodrigues-Pinto, Eduardo; Ferreira-Silva, Joel; Fugazza, Alessandro; Capogreco, Antonio; Repici, Alessandro; Everett, Simon; Albers, David; Schumacher, Brigitte; Gines, Angels; Siersema, Peter D.; Macedo, Guilherme (Endoscopy International Open, 2021)
Background and study aims The impact of COVID-19 mitigation measures on stent placement procedures has not yet been reported. The aim of this study was to assess the impact of COVID-19 mitigation measures on upper stenting during SARS-CoV-2 outbreak, as well as the use of personal protection equipment (PPE) and risk of contamination for patients and staff.Patients and methods This was a multicenter, retrospective study of consecutive patients who underwent stent placement for upper gastrointestinal obstruction during the second half of SARS-CoV-2 outbreak period in comparison to same period one year before.Results A total of 29 stents were placed for upper gastrointestinal obstruction during the study period, corresponding to an increase of 241 % comparing to the same period in 2019 (n = 12). No significant major differences were found between the two time periods regarding patients’ baseline characteristics, post-stenting management and number of staff involved in stent placement. Fellows’ involvement was significantly lower in 2020 compared to 2019 (21 % vs 67 %; P = 0.01). The majority of procedures were performed using FFP2 /FFP3 mask (76 %), protective eyewear (86 %), two pairs of gloves (65 %), hairnet (76 %) and full disposable gowns (90 %). One patient tested positive for SARS-CoV-2 after the procedure. None of the medical staff involved in stenting procedures developed COVID-19 14 days after procedure.Conclusion Upper gastrointestinal stenting increased during the SARS-CoV-2 outbreak period, which could be related to yearly variation on the number of procedures or reflect a change of oncologic treatment practice during COVID times.